Diminished CD4+/CD25+T cell and increased IFN-gamma levels occur in dogs vaccinated with Leishmune (R) in an endemic area for visceral leishmaniasis - Felix de Lima, Valeria Marcal [UNESP]; Ikeda, Fabiana Augusta [UNESP]; Rossi, Claudio N. [UNESP]; Feitosa, Mary Marcondes [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP]; Nunes, Caris Maroni [UNESP]; Goto, Hiro (Elsevier B.V., 2010)
The Leishmune (R) vaccine has been used in endemic areas to prevent canine visceral leishmaniasis in Brazil, but cytokine production induced by vaccination has rarely been investigated in dogs. This study aimed to evaluate the immune response of dogs vaccinated with Leishmune FML vaccine (Fort Dodge) against total antigen of Leishmania (Leishmania) chagasi (TAg) and FML. Twenty healthy dogs from Aracatuba, São Paulo, Brazil, an endemic leishmaniasis area, received three consecutive subcutaneous injection of Leishmune vaccine at 21-day intervals. PBMC were isolated before and 10 days after completing vaccination and lymphoproliferative response and antibody production against FML or total promastigote antigen were tested. Cytokines IFN-gamma, IL-4 and TNF-alpha were measured in culture supernatant and CD4+/CD25+ and CD8+/CD25+ T cell presence was determined. Analysis of the data indicated that the vaccine conferred humoral responses (100%) against both antigens and cellular immunity to FML (85%) and total antigen (80%), the supernatant of cultured cells stimulated with TAg and FML showed an increase in IFN-gamma (P < 0.05), and the vaccine reduced CD4+/CD25+ T cell presence compared to that observed before vaccination. These responses may constitute part of the immune mechanism induced by Leishmune. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Visceral Leishmaniasis; Vaccine; Th1 response; Cytokines; Zoonosis